A Qualitative Analysis of Violence Against Women in Politics Expressed As Female Misogyny in Mexico - Barraza Cárdenas, Paloma Cecilia; Barraza Cárdenas, Luis (Perfiles de las Ciencias Sociales, 2023)
Despite politics’ configuration as a crucial element in the process of female self-determination, this space has consistently been insecure, hostile, and aggressive for women in Mexico. Female politicians often face multiple obstacles and difficulties when carrying out activities of public or electoral nature. Violence in this context is known as ’Violence Against Women in Politics’. Furthermore, the violence is not solely perpetrated by men as the dominant group, but also by political parties, government institutions, media, and in some instances, women themselves. This last issue can be identified as ’female misogyny’, which describes when women execute acts of violence towards other women. However, research on the subject tends to focus on violence against women perpetrated by men or patriarchal organizations, and therefore few studies have attempted to explore this phenomenon in the political arena. In this context, this analytical essay examines ’Violence Against Women in Politics’ expressed as ’female misogyny’ in the specific context of Durango, Mexico, through a qualitative approach based on long interviews with female politicians. The preliminary research results illustrate that violence, regardless of perpetrator, is detrimental to women’s participation in politics and therefore ’female misogyny’ constitutes an important part of the challenges faced by women in politics. Nevertheless, it is argued that this issue requires analysis from a gendered perspective and acknowledgment that it does not exist in isolation but occurs within global and systemic dynamics.